Effectiveness of inosine pranobex in the treatment and prevention of infectious diseases (system review) - I. V. Babachenko (Журнал инфектологии)
The purpose of the article is a systematic review of studies conducted in recent decades in children and adults, with an emphasis on domestic works, on the use of inosine pranobex preparations, in the treatment of infectious diseases. The clinical and immunological effectiveness of inosine pranobex in the treatment and prevention of relapses in patients with recurrent respiratory viral infections against the background of persistent herpesviruses types 4-6 has been demonstrated. Using the example of multicenter comparative as well as placebo-controlled studies, not only the effectiveness, but also the safety of long-term courses of therapy is shown. A promising direction is the use of inosine pranobex in the treatment of COVID-19 and post-Covid conditions, taking into account its immunomodulatory effect without the risk of increasing the “cytokine storm”, as well as studies of the direct antiviral effect on the SARS-CoV-2 virus in vitro.